Antiacne Effects of PVA/ZnO Composite Nanofibers Crosslinked by Citric Acid for Facial Sheet Masks - Soyeon Jeong; Seong-Geun Oh (International Journal of Polymer Science)
The water-insoluble polyvinyl alcohol (PVA) nanofibers containing ZnO nanoparticles were prepared by an electrospinning technique for antiacne facial masks. Zinc oxide (ZnO) nanoparticles prepared by a sol-gel method were dispersed in aqueous PVA and citric acid solution for electrospinning. The electrospun nanofibers were treated at 160°C to induce the thermal crosslinking between PVA and citric acid. The crosslinked PVA with citric acid become water-insoluble, which can be used for facial masks. PVA/ZnO composite nanofibers were characterized by structural and morphological analysis techniques including Fourier transform infrared spectroscopy (FT-IR), field-emission scanning electron microscopy (FE-SEM), and transmission electron microscopy (TEM). Also, the swelling ratios according to the ZnO content (0, 1, 4, and 7 wt.% with respect to PVA) were measured. Antibacterial activity tests were also studied. The clear zone of Cutibacterium acnes of PVA/ZnO 7% nanofibers was 2.25 mm, indicating antiacne activities of nanofibers.